Inverse vulcanised polysulphide adsorbent from waste cooking palm oil for cu2+ removal - Mohd Faizal, Ali; Libat, Nancy Nubur; Hannah Nisa, Adawiyah; Nayeem, Abdullah; Jun Haslinda, Shariffuddin (Malaysian Palm Oil Board, 2025)
Heavy metals are considered to be toxic to humans. Commonly produced by petrochemical plants and pesticide productions, various techniques have been utilised to treat wastewater contaminated with heavy metal such as copper (Cu2+). This article focuses on using adsorption by utilising polysulphide adsorbent to treat wastewater via inverse vulcanisation. The huge amount of waste cooking palm oil (WCO) that is generated daily in Malaysia has motivated the study to produce a low-cost adsorbent with high removal efficiency. The polysulphide adsorbent was prepared with sulphur powder and waste cooking oil with a ratio of 9:1. The effect of contact time, initial Cu2+ concentration, and adsorbent dosage were studied using a batch adsorption process. The highest removal efficiency was 77.81% obtained while using 5 g of adsorbent dosage to treat 5 mg/L of Cu2+ aqueous solution. The Freundlich and Langmuir isotherm was used for modelling Cu2+ adsorption in an aqueous medium which was modelled best by the Langmuir isotherm. Overall, these results confirmed polysulphide as a low-cost and potential adsorbent to remove Cu2+ from wastewater.